ACADEMIC STAFF UNION VERSUS GOVERNMENT NEGOTIATION STRATEGIES: A VERITABLE TOOL FOR SUSTAINING INDUSTRIAL HARMONY IN ONDO STATE SECONDARY SCHOOLS, NIGERIA - Adekola, Adetola Adeniyi; Olowo, Busuyi Francis; Ajadi, Olugbenga Timothy (Sanata Dharma University Yogyakarta, 2021)
The study assessed negotiation strategies adopted by ASUSS and government for sustaining industrial harmony in Ondo State secondary school, Nigeria. The study adopted the survey research design using quantitative approach. The population for the study comprised 300 Principals, 600 Vice-Principals and 13,000 teachers from the 300 secondary schools in Ondo State. The sample was made up of 1500 respondents which comprised 90 principals, 180 vice-principals and 1,230 teachers using multistage sampling procedure. An instrument was use to gather data. The data collected were analysed using descriptive statistics. The findings of the study established that the causes of industrial disharmony between ASUSS and Ondo State Government were inadequate teaching and infrastructural materials (96.1%), unfavourable salary structure applicable in the State (97.3%), undue interference of government in union leadership and Government non-implementation of concluded agreements between ASUSS and Ondo State Government (93%). The findings also showed that the causes of the industrial disharmony have made ASUSS and Ondo State Government to have frequent disharmony annually (76.9%), every five years (76.7%), and biennially (76.7%). The results also indicated that the various negotiation strategies that have been adopted by ASUSS and government which include mediation (88.10%), conciliation (62.20%), arbitration (53.6%), formal Inquiry (99%) and reference to the National Industrial Court (99.10%). The results equally showed that the most effective strategies that frequently used in enhancing industrial harmony were board of inquiry (52%) and collective agreement (93,7%). The study concluded that mediation, conciliation, arbitration, formal inquiry and reference to the National Industrial Court were the ASUSS and Ondo State Government negotiation strategies as a means of ensuring industrial harmony in Ondo State secondary schools